Protection Of Women Against Online-Based Shopping Fraud - Hervina Puspitosari; Mas Anienda Tien Fitriyah (Fakultas Hukum, UPN Veteran Jawa Timur, 2021)
Online shop is a popular shopping choice. attractive to consumers without having to visit the store directly, through internet applications can be easily accessed and ordered at a price offer that is sometimes also much cheaper than shopping directly coming to the store. However, the various conveniences offered in reality also cause various problems related to the protection of consumers in transactions at online shops, which oftentimes consumers also experience fraud, whether the goods have not arrived that have been ordered and paid for or the goods arrived but are not in accordance with what was ordered. There are still many cases of online buying and selling fraud, efforts are needed to reformulate existing regulations that have not been able to accommodate the interests of consumers, so it is also necessary to change the Consumer Protection Act which is more secure in providing legal protection to consumers in online buying and selling transactions as well as regulation of business actors. that adapts to the development of information technology and social changes in society.